Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

Discovery of swertimusins A‒D: Four pairs of rearranged nor-secoiridoid derivatives with a hexahydrofuro[2,3-b]furan ring from Swertia mussotii - Xue Cheng; Qi-Feng Zhang; Rui-Kang Tan; Wen-Di Wang; Yu-Rui Dou; Jia-Yi Wei; Ke-Xun She; Xiao-Feng He (Phytochemistry, 2026)

Reinforcement-Learning-Based Adaptive PID Depth Control for Underwater Vehicles Against Buoyancy Variations - Jian Wang; Shuxue Yan; Honghao Bao; Cong Chen; Deyong Yu; Jixu Li; Xi Chen; Rui Dou; Yuangui Tang; Shuo Li (Journal of Marine Science and Engineering, 2026)
Underwater vehicles performing sampling tasks often encounter significant buoyancy variations due to payload adjustments and environmental changes, which severely challenge the stability and accuracy of controllers. To address this issue, this paper proposes a hybrid control framework that integrates Proximal Policy Optimization (PPO) with adaptive PID tuning. The framework employs PPO to dynamically adjust PID parameters online while incorporating output saturation, stepwise quantization, and dead zone filtering to ensure control safety and actuator longevity. A dual-error state representation—combining instantaneous error and its derivative—along with actuator command buffering is introduced to compensate for system lag and inertia. Comparative simulations and experimental tests demonstrate that the proposed method achieves faster convergence, lower steady-state error, and smoother control signals compared to both conventional PID and pure PPO-based control. The framework is validated through pool tests and field trials, confirming its robustness under realistic hydrodynamic disturbances. This work provides a practical and safe solution for adaptive depth control of sampling-capable AUVs operating in dynamic underwater environments.

Composite hydrogel microspheres modulate intestinal inflammation via releasing HA modified liposomes@4-OI targeting M1 macrophages - Shuanghong Yang; Ze Li; Guiwen Qu; Liting Deng; Liuqing Dou; Sicheng Li; Yitian Teng; Luqiao Huang; Haohui Li; Kang Chen; Jinpeng Zhang; Rui Ma; et al. (Chemical Engineering Journal, 2026)